The Existence of the Nahdlatul Ulama Party in the Guided Democracy Era - Rina Andriani Hidayat (Journal of Nahdlatul Ulama Studies, 2022)
This paper was motivated by the success of Nahdlatul Ulama to become the most prominent Islamic political party during the Guided Democracy period. In addition, at the time, Nahdlatul Ulama Party (PNU) played an essential role in the national political scene as one of the main components of the "Nasakom" politics promoted by President Soekarno from religious circles. Even the PNU has the right to have representatives in all government commissions and organizations.The main problem in this paper was: why did PNU manage to maintain its existence as an Islamic political party and become one of the main components of â€œNasakomâ€ politics during the Guided Democracy period? Based on these problems, several research questions were formulated: Why did NU turn into a political party? How was Sukarno's political policy during the Guided Democracy? What was the PNU's political stance during the Guided Democracy? The political existence of the PNU during the Guided Democracy was written using the historical method with a behavioristic approach. As for the spatial and temporal scope of the Soekarno government's research during the Guided Democracy period (1959-1965). The results showed that the PNU's stance was motivated by the attitude of PNU's dissatisfaction with the political policies of the Masyumi Party. PNU's participation in the 1955 General Election made PNU the third-largest political party after the PNI and the Masyumi Party. During the Guided Democracy period, the PNU tried to maintain its existence by supporting every political policy of Soekarno through support based on the principles of ushul fiqh, namely wisdom, flexibility, and moderation. Even in the decision-making process, there is often a bargaining process.